2022
DOI: 10.7554/elife.76027
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface adhesion on the macroscopic wrinkling of biofilms

Abstract: Biofilms, bacterial communities of cells encased by a self-produced matrix, exhibit a variety of three-dimensional structures. Specifically, channel networks formed within the bulk of the biofilm have been identified to play an important role in the colonies' viability by promoting the transport of nutrients and chemicals. Here, we study channel formation and focus on the role of the adhesion of the biofilm matrix to the substrate in Pseudomonas aeruginosa biofilms grown under constant flow in microfluidic cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…(2) the bottom glass coverslip has a negative surface charge whereas PDMS surface is close to neutral, so negatively charged bacterial surfaces tend to attach better to PDMS surfaces. Consistently, a previous study also observed bio lm observation on the PDMS surfaces but not on the glass surfaces 41 .…”
Section: Bio Lm Development On the Sidewalls And Top Surfaces Of The ...supporting
confidence: 89%
“…(2) the bottom glass coverslip has a negative surface charge whereas PDMS surface is close to neutral, so negatively charged bacterial surfaces tend to attach better to PDMS surfaces. Consistently, a previous study also observed bio lm observation on the PDMS surfaces but not on the glass surfaces 41 .…”
Section: Bio Lm Development On the Sidewalls And Top Surfaces Of The ...supporting
confidence: 89%
“…Many other biofilms, such as those used in moving‐bed biofilm reactors (MBBRs) (Bassin et al, 2012), are beneficial because they remove contaminants and excess nutrients from wastewater (Zhu et al, 2010). Biofilms can form different morphologies, including thin film structures (Coyte et al, 2017), wrinkles (Geisel et al, 2022), ripples (Nguyen et al, 2005), and streamers (Drescher et al, 2013; Parvinzadeh Gashti et al, 2015). Fundamental understanding of biofilm morphology is critical to predict and manipulate the function of biofilms (Recupido et al, 2020; Trejo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To best of our knowledge, no other study presented a synthetic oscillator capable of transforming such dynamic phenomena into spatial patterns. Interestingly, spatial period-doublings have been used to describe wrinkle formation [52, 53] [54] occurring in skin folding [55], mucous membranes [56], the convoluted shape of the brain [57, 58] and biofilm formation [59, 60]. Our circuit could thus be used to generate differential stress conditions in a cell layer in order to reproduce and control wrinkle patterns.…”
Section: Discussionmentioning
confidence: 99%